Joint action of two RNA degradation pathways controls the timing of maternal transcript elimination at the midblastula transition in Drosophila melanogaster. - Bashirullah, A.; Halsell, S.R.; Cooperstock, R.L.; Kloc, M.; Karaiskakis, A.; Fisher, W.W.; Fu, W.; Hamilton, J.K.; Etkin, L.D.; Lipshitz, H.D. (The EMBO Journal, 1999)
Maternally synthesized RNAs program early embryonic development in many animals. These RNAs are degraded rapidly by the midblastula transition (MBT), allowing genetic control of development to pass to zygotically synthesized transcripts. Here we show that in the early embryo of Drosophila melanogaster, there are two independent RNA degradation pathways, either of which is sufficient for transcript elimination. However, only the concerted action of both pathways leads to elimination of transcripts with the correct timing, at the MBT. The first pathway is maternally encoded, is targeted to specific classes of mRNAs through cis-acting elements in the 3'-untranslated region and is conserved in Xenopus laevis. The second pathway is activated 2 h after fertilization and functions together with the maternal pathway to ensure that transcripts are degraded by the MBT.